ChemInform Abstract: α‐Arylation/Heteroarylation of Chiral α‐Aminomethyltrifluoroborates by Synergistic Iridium Photoredox/Nickel Cross‐Coupling Catalysis. Issue 19 (21st April 2016) - El Khatib, Mirna; Serafim, Ricardo Augusto Massarico; Molander, Gary A.
Abstract: Novel enantiopure amino acid derivatives are obtained starting from inexpensive natural amino acids.